Clinical Outcomes and Complications of Simultaneous Bilateral Total Knee Arthroplasty Compared with Staged Total Knee Arthroplasty in Patients with Severe Knee Osteoarthritis - Othdeh Samuel Halomoan Siahaan; Ludwig Andribert Powantia Pontoh; Ismail Hadisoebroto Dilogo; Endro Tomo Sumargono (CV. Publikasi Indonesia, 2026)
Osteoarthritis (OA), the most common degenerative joint disease and a leading cause of disability, primarily affects the knee joint. In severe knee OA, total knee arthroplasty (TKA) is an effective treatment option; bilateral cases may be managed through simultaneous bilateral total knee arthroplasty (simBTKA) or staged total knee arthroplasty (staTKA), depending on patient characteristics and risk profiles. simBTKA may reduce overall treatment duration and healthcare costs but is associated with a higher risk of short-term mortality, venous thromboembolism, increased transfusion requirements, and more complex rehabilitation. Evidence remains limited regarding which patients derive the greatest benefit, medium- to long-term outcomes (patient-reported outcome measures [PROMs], including the Oxford Knee Score [OKS], Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC], and range of motion [ROM]), and total treatment costs. This study aimed to compare the clinical outcomes and complications of simBTKA and staTKA in patients with severe knee OA using a retrospective cohort design based on medical records of patients with severe bilateral OA who underwent either simBTKA or staTKA at RSCM, Fatmawati Central General Hospital, and St. Carolus Hospital between January 2021 and September 2024, according to predefined eligibility criteria. The assessed outcomes included OKS, WOMAC, ROM, length of stay (LOS), and complication incidence, which were analyzed using SPSS version 25 for Windows. Before adjustment, WOMAC scores were higher in the simBTKA group than in the staTKA group (median 28 vs. 14; p = 0.012), with no significant differences observed in OKS or ROM. Following ANCOVA adjustment, WOMAC scores were lower in the simBTKA group than in the staTKA group (adjusted mean 22.31 vs. 28.72; p = 0.04), and ROM was superior in the simBTKA group (adjusted mean 119.42 vs. 112.80; p = 0.03). Blood loss was greater in the staTKA group than in the simBTKA group (median 650 vs. 200 cc; p < 0.001). Overall, after adjustment, WOMAC scores and ROM outcomes were better in the simBTKA group than in the staTKA group, whereas blood loss was greater in the staTKA group.